Efficacy of adeno-associated virus gene therapy in a MNGIE murine model enhanced by chronic exposure to nucleosides - Ferran Vila-Julià; Raquel Cabrera-Pérez; Yolanda Cámara; Miguel Molina-Berenguer; Silvia Lope-Piedrafita; Michio Hirano; Federico Mingozzi; Javier Torres-Torronteras; Ramon Martí (EBioMedicine, 2020)
Background: Preclinical studies have shown that gene therapy is a feasible approach to treat mitochondrial neurogastrointestinal encephalomyopathy (MNGIE). However, the genetic murine model of the disease (Tymp/Upp1 double knockout, dKO) has a limited functional phenotype beyond the metabolic imbalances, and so the studies showing efficacy of gene therapy have relied almost exclusively on demonstrating correction of the biochemical phenotype. Chronic oral administration of thymidine (dThd) and deoxyuridine (dUrd) to dKO mice deteriorates the phenotype of the animals, providing a better model to test therapy approaches. Methods: dKO mice were treated with both dThd and dUrd in drinking water from weaning until the end of the study. At 8 - 11 weeks of age, mice were treated with several doses of adeno-associated virus (AAV) serotype 8 vector carrying the human TYMP coding sequence under the control of different liver-specific promoters (TBG, AAT, or HLP). The biochemical profile and functional phenotype were studied over the life of the animals. Findings: Nucleoside exposure resulted in 30-fold higher plasma nucleoside levels in dKO mice compared with non-exposed wild type mice. AAV-treatment provided elevated TP activity in liver and lowered systemic nucleoside levels in exposed dKO mice. Exposed dKO mice had enlarged brain ventricles (assessed by magnetic resonance imaging) and motor impairment (rotarod test); both were prevented by AAV treatment. Among all promoters tested, AAT showed the best efficacy. Interpretation: Our results show that AAV-mediated gene therapy restores the biochemical homeostasis in the murine model of MNGIE and, for the first time, demonstrate that this treatment improves the functional phenotype. Funding: This work was funded in part by the Spanish Instituto de Salud Carlos III, and the Generalitat de Catalunya. The disclosed funders had no role in study design, data collection and analysis, decision to publish, or preparation of the manuscript.